1987
DOI: 10.1590/s0074-02761987000300009
|View full text |Cite
|
Sign up to set email alerts
|

Role of divalent cations, pH, cytoskeleton componentes and surface charge on the adhesion of Trichomonas vaginalis to a polystyrene substrate

Abstract: The process of adhesion of three different strains of Trichomonas vaginalis to a polystyrene substrate was analysed. The process of adhesion was dependent on the time of incubation and the pH of the phosphate-buffered solution (PBS) in which the parasites were suspended. The highest indices of adhesion were observed after an incubation time of 60 min at pH 6.6. The adhesion index increased when the parasites were incubated in the presence of culture media or when Ca++ or Mg++ was added to the PBS solution, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Since both polystyrene and the cell surface of trichomonads are negatively charged (24,29,45), laminin could act by rendering the plastic surface less negative or even positive. Our results showed otherwise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both polystyrene and the cell surface of trichomonads are negatively charged (24,29,45), laminin could act by rendering the plastic surface less negative or even positive. Our results showed otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 hr ofincubation nonadherent parasites were aspirated with a Pasteur pipette, and 2 ml of PBS containing 2.5% (vol/vol) glutaraldehyde was added. Adherent parasites were counted in an inverted microscope by using a transparent grid with 4-mm2 squares placed below the plastic dishes (29 (14). Laminin P1 fragment was prepared according to Rohde et al (31).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated in several works that Trichomonas vaginalis can adhere to plastic surfaces in the presence of various agents and under different experimental conditions [24][25][26][27][28]. In addition, one group [28] demonstrated that the parasite can adhere to polystyrene, intrauterine devices, and vaginal rings.…”
Section: Monolayer Formation By T Vaginalismentioning
confidence: 99%